If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18-6x=2x-6
We move all terms to the left:
18-6x-(2x-6)=0
We get rid of parentheses
-6x-2x+6+18=0
We add all the numbers together, and all the variables
-8x+24=0
We move all terms containing x to the left, all other terms to the right
-8x=-24
x=-24/-8
x=+3
| 3(h−66)=84 | | a÷5+4=14a= | | 19=d3+ 15 | | 41+5x=61 | | 96=31+5z | | 12-5y=22 | | 10m-17=63m= | | 5(x+10)+4x=3x+2 | | w−55=33 | | 12n−8+3n=52 | | 4(5m−1)=84 | | 210/n=46/10 | | 3(x+6)=3x+15 | | 12=r+3 | | x+16=13x | | 4(5w−1)=84 | | m/3.2=8m= | | 0.6x-1.9=02x+0.5 | | 24x=2,040 | | 2x+105=105 | | 20+10x+10=15x+20-4x | | 3a=21+30 | | 7(1-8x)=5x+7 | | 24=–6a–6 | | (1,06)^x=3 | | 20x-1=x+11 | | g÷5.73=8 | | x-4.5=6.74 | | 23+6x=5 | | ¾x+5=14 | | 5+b=62 | | 3x-4(x+2)=18 |